2022
DOI: 10.1186/s13256-022-03337-3
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole-induced galactorrhea in kidney transplant patients—a case report

Abstract: Background Omeprazole belongs to the pharmacological classifications of proton pump inhibitors and is a widely used medicine. All proton pump inhibitors have a common mechanism of action and are prodrugs that require activation in an acidic environment. Omeprazole is extensively metabolized in the liver by cytochrome 2C19 and cytochrome 3A4, which are responsible for drug interactions. Omeprazole-induced galactorrhea is a rare adverse event of drug metabolism and is often underreported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…While, protective factors of the stomach include any molecules that induce gastric mucus secretion and preserve intact mucosa in case of changes in the pH, temperature, and microbial infection that can stimulate the inflammatory process ( Bitar and Moussa, 2022 ). Synthetic chemicals (Omeprazole) is a well-known proton pump inhibitor (PPI) used widely for gastric disorders, but recent studies have reported several adverse effects of this drug including osteoporotic fracture ( Lespessailles and Toumi, 2022 ), heart attack ( Oo and Lim, 2022 ), and galactorrhea in kidney transplant cases ( Dorji et al, 2022 ). Recently, a population based-study revealed that significant correlation between intake duration intake and dose-dependence of administering PPI with the increasing incidence of stomach cancer ( Cheung et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While, protective factors of the stomach include any molecules that induce gastric mucus secretion and preserve intact mucosa in case of changes in the pH, temperature, and microbial infection that can stimulate the inflammatory process ( Bitar and Moussa, 2022 ). Synthetic chemicals (Omeprazole) is a well-known proton pump inhibitor (PPI) used widely for gastric disorders, but recent studies have reported several adverse effects of this drug including osteoporotic fracture ( Lespessailles and Toumi, 2022 ), heart attack ( Oo and Lim, 2022 ), and galactorrhea in kidney transplant cases ( Dorji et al, 2022 ). Recently, a population based-study revealed that significant correlation between intake duration intake and dose-dependence of administering PPI with the increasing incidence of stomach cancer ( Cheung et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%